Intra-voxel incoherent motion biomarker repeatability in healthy volunteers and sensitivity to chemoradiotherapy-induced changes in patients with uterine cervical cancer - McHugh, Damien J.; Datta, Anubhav; Dubec, Michael J.; Buckley, David L.; Little, Ross A.; Berks, Michael; Cheung, Susan; Haslett, Kate; Barraclough, Lisa; West, Catharine M. L.; Choudhury, Ananya; Hoskin, Peter; et al. (Frontiers in Oncology, 2025)
Intra-voxel incoherent motion (IVIM) biomarkers require validation for translation into clinical practice. This work evaluates repeatability and sensitivity to treatment of IVIM biomarkers in the uterine cervix, and assesses suitability of the IVIM model. Six healthy volunteers underwent two scans to evaluate repeatability. Eight patients with stage IIB-IVA cervical squamous cell carcinoma were scanned pre-treatment, and at weeks 3 and 5 into treatment. IVIM and apparent diffusion coefficient (ADC) model fits were compared using the corrected Akaike information criterion (AICc). Tissue diffusion coefficient, D, perfusion signal fraction, f, and pIVIM, the fraction of voxels better described by the IVIM model, were measured. ADCs calculated with minimum b-values of 0 (ADCb0) and 150 s/mm2 (ADCb150) were compared with f to assess sensitivity to perfusion. Model preference maps qualitatively reflected physiological characteristics of different tissues. Healthy cervix within-subject coefficients of variation were 8% (D), 15% (f), and 12% (pIVIM). Tumour D increased from baseline to week 3 (p = 0.02). Baseline pIVIM showed large inter-patient variability (range: 0.13-0.68), which persisted throughout treatment. The difference between ADCb0 and ADCb150 correlated with f (repeated measures correlation coefficient r=0.76, p = 0.002). IVIM biomarkers are repeatable in healthy cervix tissue. Tumour D is sensitive to early therapy-induced changes. The IVIM model is not favoured in all tumour voxels, indicating the presence of heterogeneous tumour microenvironments. ADC calculated using b = 0 s/mm2 can be influenced by a perfusion-dependent bias. Not all tumour voxels are best described by the IVIM model. ADC in cervical tumours can suffer from perfusion-dependent bias.